Wild Animals as Assets in Conservation Institutions: A Phenomenological Study at Secret Zoo - Winda Ayu Anggraini; Eka Ananta Sidharta; Puji Handayati (AIBPM Publisher, 2020)
The objective of this study was to determine the meaning of wild animals as assets in conservation organizations. This research was qualitative research using a phenomenological approach. The interviewees of this study were from the legality department, animal reporting, and field supervisors at Secret Zoo. The results showed that wild animals were endangered animals that could not be traded freely, so that valuation, disclosure, and reporting activities could not be achieved through the applicable biological asset standards. In addition, wild animals have no selling value as a measure of their assets, thus the Secret Zoo used both exchange value and conservation value to support the management of assets. Therefore, wild animal assets could not be commercially recognized and business activities in conservation institutions required other components excluded from animals.